Utilization of Innovative Banking Resources in the Financial Sphere - Yuldasheva Dilorom Shakhzod Kizi (International Journal on Integrated Education, 2023)
A significant role in the sustainable development of the reproductive processes of the regional economy is played by banking institutions, the functioning of which is based on the achievement of strategic goals of sustainable development, and maintaining the dynamic balance of the social, economic and environmental environment. The ongoing changes in the modern economic space affect all spheres of functioning of industry markets and sectors of public relations. The emerging problems associated with achieving economic balance and sustainable development of industry markets require the formation of new methodological approaches to their solution. A significant role in ensuring the sustainable development of the national economy is played by the banking system, which allows you to involve the existing financial potential of various economic agents and transform them into investment resources aimed at modernizing and expanding social reproduction, achieving target proportions of economic growth.